UPPER-STRUCTURE DESIGN OF SERPONG RENT OFFICE NORTHERN PODIUM AND TOWER - VANIA MARBUN, CHRISTY
PT.Paramound Land as one of the large company in Indonesia plans to develop its subsidiary by providing 32000 m2 lands area in Gading Serpong, Tangerang. One of the their development is building the first Serpong rental office as an office building which provide the supporting facilities for both workers and visitors. Serpong rental office has 21 floors and 1 roof top with height almost reach 84.25 m. Serpong Rental Office is located in prone of earthquake areas and has a soft soil conditions, so itÃ‚Â’s appertain to the Seismic Design Category D (SDC D). Hence, the structural system which is used in the structure design is a dual structure system. This dual structure system consists of Special Basic Frame Moment Resistance System (SBFRS), and Special Structural Wall System (SSWS) The modeling structure of Serpong Rental Office is by using the ETABS 2015 software and the used of analytical procedure is spectrum response analysis. This modeling is based on SNI 1726-2012 about terms of earthquake resistance planning for building and non-building structures. The result of structure period is 1.861 for x and 1.82 for y. The upper structure analysis of the between floors, eccentricity, horizontal irregularities, and vertical irregularities has been accomplished, and the P-Delta effect is not taken into the calculation. Detailed design of structural component elements is done based on SNI 2847-2013 for structural elements of beams, columns, plates, and shear walls. Column design assisted by PCACOL software and plate design assisted by SAFE 2016 software